Monitoring, Analzying, and Visualizing Distributed Computing Clusters - Stupka, John (My University, 2015)
We present a web service that aggregates information from multiple machines, organizes it in a database, and generates visualizations that can be shown on low-power systems such as the Raspberry Pi.
Color poster with text, images, charts, and photographs.
Keywords: Systems administration; Clusters; Raspberry Pi; Distributed systems; Computing clusters; Posters